2002
DOI: 10.1093/jxb/erf044
|View full text |Cite
|
Sign up to set email alerts
|

Increasing antioxidant levels in tomatoes through modification of the flavonoid biosynthetic pathway

Abstract: Flavonoids are a diverse group of phenolic secondary metabolites that occur naturally in plants and therefore form an integral component of the human diet. Many of the compounds belonging to this group are potent antioxidants in vitro and epidemiological studies suggest a direct correlation between high flavonoid intake and decreased risk of cardiovascular disease, cancer and other age-related diseases. Enhancing flavonoid biosynthesis in chosen crops may provide new raw materials that have the potential to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(156 citation statements)
references
References 23 publications
7
129
1
7
Order By: Relevance
“…Epidemiological studies have consistently shown an inverse association between consumption of some nutritional flavonoids and the risk of human cancers at many sites [6][7][8][9]. NAR has been widely studied and has been reported to be an antioxidant [10,11] …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have consistently shown an inverse association between consumption of some nutritional flavonoids and the risk of human cancers at many sites [6][7][8][9]. NAR has been widely studied and has been reported to be an antioxidant [10,11] …”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl radical generated from hydrogen peroxide reacting with different transition metals is particularly damaging to DNA, leading to mutagenesis and carcinogenesis (2). Voluminous research has been carried out to discover new antioxidant compounds from plant and animal origin to prevent free radical damage (3)(4)(5)(6). Polypeptide with antioxidant property has also been reported in Chlamys farreri (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to gain up to a 78-fold increase in total fruit flavonols through ectopic expression of a single structural gene CHI (Verhoeyen at al., 2002).…”
Section: Engineering Of Structural Genesmentioning
confidence: 99%